Point-of-care NT-proBNP monitoring for heart failure: observational feasibility study in primary care - Chami, J; Fleming, S; Taylor, C; Bankhead, C; James, T; Shine, B; McLellan, J; Hobbs, FDR; Perera, R (Royal College of General Practitioners, 2022)
Background Around one million individuals in the UK have heart failure (HF), a chronic disease that causes significant morbidity and mortality. N-terminal pro–B-type natriuretic peptide (NT-proBNP) monitoring could help improve the care of patients with HF in the community. Aim The aim of this study is to provide evidence to support the routine use of point-of-care (POC) NT-proBNP monitoring in primary care. Design & setting In this observational cohort study, the Roche Cobas h 232 POC device was used to measure NT-proBNP in 27 patients with HF at 0, 6 and 12 months, with a subset reanalysed in the laboratory for comparison. Method Data were analysed for within- and between-person variability and concordance with laboratory readings using Passing–Bablok regression. GPs reported whether POC results impacted clinical decision-making, and patients indicated their willingness to participate in long-term cohort studies using the Likert acceptability scale. Results Within-person variability in POC NT-proBNP over 12 months was 881 pg/mL (95% C.I. 380–1382 pg/mL). Between-person variability was 1972 pg/mL (95% C.I. 1,525–2791 pg/mL). Passing–Bablok regression showed no significant systematic difference between POC and laboratory measurements. Patients indicated a high level of acceptability, and GP decision-making was affected for at least one visit in a third of patients. Conclusion Within person variability in POC NT-proBNP is around half of between-person variability, so detecting changes could be of use in HF management. High patient acceptability and impact on clinical decision-making warrant further investigation in a larger long-term cohort study.